(untitled) (The Batuk, 2026)
This research explores the influence of parental socialization, financial literacy, and self-control on the saving behavior of Nepali youth. It used a quantitative cross-sectional research design, which incorporated structured questionnaires to gather data from 402 respondents. The findings suggest that all three predictors have a direct influence on saving behavior, with self-control being the strongest contributor. In particular, parental socialization (B = 0.300, β = 0.295, p < 0.001) positively influences saving behavior showing the critical role of parental financial discussions and role modelling in helping to shape their saving behavior. Financial literacy (B = 0.274, β = 0.282, p < 0.001) showed a significant positive contributor to saving behavior confirming that with more financial knowledge parents save more and do then make saving behavior. Self-control (B = 0.302, β = 0.308, p < 0.05) is also identified as an important contributor to saving behavior highlighting the impact of self-discipline, in a world where consumer temptation is easy to indulge in. The integrated model accounted for 42.7% of savings behavior, suggests that socio-psychological influence play a significant part in making financial decisions.